Complicações físico-funcionais pós-tratamento cirúrgico do câncer de mama: estudo descritivo e retrospectivo - Silva, Amanda Estevao Da [UNIFESP] (2020)
Introduction: The ideal treatment for breast cancer should be performed by a multidisciplinary team and aims at the overall approach of the patient. It is usually prolonged and can cause relevant changes in the patient’s life, such as limiting shoulder movement, pain, lymphedema, scarring, sensory changes, phlebitis, among others. Physiotherapeutic intervention plays a fundamental role and can prevent and minimize complications, in addition to enabling functional recovery. It is of extreme importance that the physiotherapy service should know the prevalence of the main physical-functional complications and the impact of its intervention. Objective: To evaluate the main physical-functional complications after surgical treatment of breast cancer. Methods: This was a descriptive and retrospective study, carried out at the Mastology Outpatient Clinic of the Department of Gynecology of the Paulista School of Medicine (EPM), Federal University of São Paulo (UNIFESP), where patients' charts were consulted in the period of 2011 to 2016. Data on the type of surgery, pain prevalence, perimetric alterations, range of motion, evaluation of the scapulohumeral rhythm and the presence of axillary cord were obtained. Results: A total of 703 medical records were obtained, the mean age of the patients was 56 years, 50.1% were married, with mean BMI indicating weight (26.8 kg/m2) and higher prevalence of sedentary lifestyle (73.7%). The main surgery was quadrantectomy, followed by mastectomy. Pain was present, but at extremely low levels (mean VAS in PO7 was 2.55), range of motion restrictions were higher initially and functionally reversed during follow-up, scapular dysfunctions were also less prevalent (9.9%) and with a high percentage of resolution during the follow-up. The incidence of axillary cords was high (87.9%) and requires special attention. Conclusion: The study allowed to know the main physical-functional complications post-treatment of breast cancer and to demonstrate the importance and necessity of the early physiotherapy.